Beyond Criminality: Socio-Legal Dimensions and Fiqh Perspectives on Adulterated Rice Trading Practices in Contemporary Palangka Raya - nababan, jessica; Suriani, Rollys; F. Dewi, Yurika (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2026)
This research examines the implementation of Article 378 of the Indonesian Criminal Code (KUHP) in handling cases of fraud in adulterated rice trading in Palangka Raya City using an empirical juridical research method. The study aims to analyze the application of criminal fraud provisions to adulterated rice trading practices and to identify the obstacles faced by law enforcement authorities in its implementation. The empirical juridical method is employed by combining a normative approach to Article 378 of the Criminal Code with field research through the collection of case data that occurred in Palangka Raya. The research findings indicate that, normatively, Article 378 of the Criminal Code is highly relevant to be applied in cases of adulterated rice, as it fulfills all elements of fraud, namely the intention to unlawfully benefit oneself, the use of deception through fake packaging and labels, and inducing consumers to hand over their money. However, empirically, implementation in Palangka Raya City faces significant obstacles, including difficulties in proving the element of intent on the part of the perpetrator, low public participation in reporting, weak inter‑agency coordination, limited resources, and an ever‑evolving modus operandi. Law enforcement authorities often prefer to use the Consumer Protection Law and the Food Law, which impose heavier sanctions. The research concludes that effective law enforcement requires the improvement of technology‑based supervision systems, strengthening coordination through special task forces, enhancing the capacity of law enforcement officers, building easily accessible reporting infrastructure, and harmonizing regulations between general criminal law and special laws in order to protect consumers from fraudulent practices in adulterated rice trading.